Soluble Host Defense Lectins in Innate Immunity to Influenza Virus. (16th May 2012) - Ng, Wy Ching; Tate, Michelle D.; Brooks, Andrew G.; Reading, Patrick C.
Abstract : Host defenses against viral infections depend on a complex interplay of innate (nonspecific) and adaptive (specific) components. In the early stages of infection, innate mechanisms represent the main line of host defense, acting to limit the spread of virus in host tissues prior to the induction of the adaptive immune response. Serum and lung fluids contain a range of lectins capable of recognizing and destroying influenza A viruses (IAV). Herein, we review the mechanisms by which soluble endogenous lectins mediate anti-IAV activity, including their role in modulating IAV-induced inflammation and disease and their potential as prophylactic and/or therapeutic treatments during severe IAV-induced disease.